Detection of asinine gammaherpesviruses in association with pulmonary fibrosis in free-ranging donkeys. (January 2022) - Maboni, Grazieli; Kelly, E. Jane; Clancy, Chad S.; De Luca, Eliana; Baldwin, Thomas J.; Van Wettere, Arnaud J.; Kane, Albert J.; Peterson, Summer; Warr, V. Gus; Bastian, Dona A.; Sanchez, Susan
A mortality event among recently captured feral donkeys ( Equus asinus ) occurred in south-central Utah in 2016. The deaths were sporadic, and clinical signs were indicative of respiratory disease, likely associated with an infectious etiology. Ten of 13 donkeys autopsied had moderate-to-severe interstitial fibrosing pneumonia, and one had pyogranulomatous pneumonia. Consensus PCRs directed toward the DNA polymerase and DNA packaging terminase subunit 1 for herpesviruses were performed followed by sequencing of the PCR amplicons and phylogenetic analysis. Asinine herpesvirus 4 (AsHV4) and 5 (AsHV5) were consistently identified in lung tissues of affected donkeys. No other herpesviruses were identified, and herpesviral DNA was not detected in lung tissues of 2 donkeys without evidence of respiratory disease. The detection of asinine gammaherpesviruses may have been associated with the lesions described. AsHV4 and AsHV5 have been reported in previous studies as novel gammaherpesviruses based on sequences obtained from donkeys with interstitial pneumonia and marked syncytial cell formation. Our findings suggest that the association of asinine gammaherpesviruses with respiratory conditions in equids deserves further attention.